Briquette of Empty Fruit Bunch Fiber as an Alternative Substitution for Binderless Fuel Methods - Handra, Nofriady; Indra, Ade (Makara Journal of Technology, 2023)
Biomass development has been a key issue for the past few decades and will remain attractive in the future because of its cleanliness, renewability, carbon neutrality, and other advantages. This study aims to determine the optimal holding time for heating system briquettes by testing the heating value of empty fruit bunches fibers. The process of this research involves the use of one unit of briquette molding equipment by providing a heating system to the mold cylinder. Fibers were manually finetuned until they reached a size of 20 mesh (0.84 mm). Densification temperature is an essential factor that could affect the combustion properties, especially the calorific value. The Arduino program is used for setting the heating resistance time of the mold, which is 15, 20, and 25 min at a temperature of 200 ºC, and the thermal controller is used to adjust the temperature variation. Results showed that the highest calorific value of the three varieties of holding time was at 25 min with a calorific value of 4480.2 cal/g, and the lowest cost at 15 min was 4022 cal/g. Meanwhile, a calorific value of 4432.5 cal/g was found at 20 min. This finding is due to the low moisture content and high charcoal content of the sample in the 25 min briquette mold. Therefore, briquettes at 25 min have a higher heating value compared with those at 15 and 20 min holding time.